Pengaruh Kesehatan dan Keselamatan Kerja terhadap Produktivitas Kerja Karyawan Bagian Teknisi PT. MADAS Elektrikal Kontraktor Tembilahan - Anggraini, Wenty; Hendriani, Susi (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2024)
This research was conducted with the aim of determining the influence of occupational health and safety variables on the work productivity of technician employees PT. MADAS Elektrikal Kontraktor Tembilahan. This type of research uses quantitative research methods with a population of 42 technician employees. This research used technician employees of PT. MADAS Elektrikal Kontraktor Tembilahan as research object. The sampling methods used a saturated sample of 42 respondents and used simple linear regression analysis for data processing. Based on the results of research conducted, it shows that occupational health and safety variables have a positive and significant effect on the work productivity of technician employees PT. MADAS Elektrikal Kontraktor Tembilahan.